A Miniaturized Ultrawideband V-Shaped Tip E-Probe for Near-Field Measurements - Mahmoud Mohammed Khodeir; Zhaowen Yan; Fuyu Zhao (Sensors, 2024)
A sensitive, miniaturized, ultrawideband probe is proposed for near-field measurements. The proposed probe is based on a new V-shaped tip design and a slope structure resulting in better field distribution and impedance matching with a span bandwidth from 10 kHz up to 52 GHz, which is compatible with ultrawideband applications. The proposed E-probe fabrication process utilizes a four-layer printed circuit board (PCB) using Rogers RO4003 (tm) and RO4450 high-performance dielectrics, with εr = 3.55 and 3.3, respectively. The probe length is 40 mm with a minimum width of 4 mm, which is suitable for narrow, complex, and integrated PCBs. The passive E-probe sensitivity is −106.29 dBm and −87.48 dBm at 2 GHz and 40 GHz, respectively. It has a very small spatial resolution of 0.5 mm at 20, 25, 30, and 35 GHz. The probe is small and cheap and can diagnose electromagnetic interference (EMI) in electronic systems such as telemetry, UAVs, and avionics.